Mengasihi Saudara - Naumi Kadarsi (FILADELFIA: Jurnal Teologi dan Pendidikan Kristen, 2020)
Strong individual traits influence humans to become a person who loves himself. The desire to actualize oneself and provide self-satisfaction results in becoming a more self-centered person. As a result something that is not in accordance with itself, people will tend to be angry or hate others because it does not match what he expected. Loving is not a new thing or command. Filadefia is a city built by a brother and given to his brother. Whereas the Philadelphian church mentioned in Revelation kitan is a faithful and diligent church obeying God's commands. Although the congregation does not have great strength in the midst of persecution that suppresses it, but his love for God shows faith and faithfulness to do God's commands. In writing, you often use the word Agape rather than philio. In this case John asserts that the command to love you proves that he is a follower of Jesus. Being a follower or disciple of Jesus means staying in God moving from death. Staying in God means following all the commands of God means not hating one another. It is not easy to carry out God's command to love you but on the basis of agape love that is the sacrifice of Jesus Christ who gave His life for friends, brothers and also called children of God. Give an example that every believer must do so that the designation of brothers, friends and children of God clearly makes a difference with the children of Satan and also proves the believer's obedience to Jesus Christ as his Lord and Savior.